2016
DOI: 10.1590/1983-40632016v4642418
|View full text |Cite
|
Sign up to set email alerts
|

Production of gladiolus submitted to gibberellic acid in a protected environment1

Abstract: Gladiolus is an important cut flower commercialized in Brazil, and the use of gibberellic acid (GA3) to cultivate it in a protected environment may promote the production of high quality flower spikes. This study aimed at evaluating the production of flower spikes and corms of gladiolus ('White Friendship' cultivar) submitted to high concentrations and application methods of gibberellic acid, in a protected environment. The experimental design was randomized blocks, in a 2 x 4 factorial arrangement, being two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Tulip bulbs treated with 100 mg L -1 GA3 sprouted in significantly less number of days, exhibited higher sprouting percentage, more plant height, leaf area, leaf chlorophyll, photosynthesis rate, flower stalk length, stalk diameter, and fresh and dry stalk weight (Ramzan et al, 2014). Carvalho-Zanão et al (2016) studied the production of gladiolus submitted to gibberellic acid in a protected environment and observed that high concentrations of GA3 are not recommended for the production of flower spikes and corms of the 'White Friendship' gladiolus cultivar.…”
Section: Gibberellinmentioning
confidence: 99%
“…Tulip bulbs treated with 100 mg L -1 GA3 sprouted in significantly less number of days, exhibited higher sprouting percentage, more plant height, leaf area, leaf chlorophyll, photosynthesis rate, flower stalk length, stalk diameter, and fresh and dry stalk weight (Ramzan et al, 2014). Carvalho-Zanão et al (2016) studied the production of gladiolus submitted to gibberellic acid in a protected environment and observed that high concentrations of GA3 are not recommended for the production of flower spikes and corms of the 'White Friendship' gladiolus cultivar.…”
Section: Gibberellinmentioning
confidence: 99%